(untitled) (Research, Society and Development, 2020)
The need to reduce the amount of dietary saturated fatty acids (SFA), made the search for replacements for these fats a very important field for research. At the search for such replacements the organogel technology has shown great potential. This study had the objective of produce reduced SFA margarines using organogel technology to structure vegetable oils. A laboratory scale process (1kg batch) were performed the margarines were produced using 80% of lipid phase (LP) and their fatty acid composition, spreadability, hardness and thermal stability were evaluated and compared to commercial samples of margarines ranging from 70 to 82% (LP). A experimental design were used to achieve a product similar to the commercial product. Using the analysis of the response surfaces it was possible to observe that the measured spreadability ranged from 0.44 up to 11.12 kg.s for the tested margarines, and from 2.46 to 3.63 kg.s for the commercial samples respectively. 0.35 up to 7.37 kg from for the consistency (1.89 – 2.78 kg for commercial samples) and 1.23 up to 35.97 N for hardness (5.78 – 7.84 N for commercial samples), based on such results a optimized formulation were produced using soybean oil and high oleic sunflower oil to achieve the same properties as the commercial products. In conclusion, it was possible to produce margarines, using organogels for oil structuring.